2014
DOI: 10.1063/1.4886675
|View full text |Cite
|
Sign up to set email alerts
|

Proposed measurement of spin currents in a GaAs crystal using the electro-optical Pockels effect

Abstract: A new method for measuring spin currents is proposed, based on the linear electro-optic (Pockels) effect caused by the additional second-order nonlinear electric susceptibility (electro-optic tensor) generated by the spin currents. The non-zero elements of electro-optic tensor induced by spin currents in GaAs crystal are calculated, and the wave coupling theory of linear electro-optic effect is used to analyze the polarization change of a probe beam. The numerical results show that, for a linearly polarized pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
1

Year Published

2015
2015
2017
2017

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 24 publications
0
5
1
Order By: Relevance
“…It can be seen that the polarization of the output beam is elliptical, which is different from the result of Zhang et al 23 Based on Eq. (23), we can investigate the state of output light in detail.…”
Section: Discussioncontrasting
confidence: 74%
See 1 more Smart Citation
“…It can be seen that the polarization of the output beam is elliptical, which is different from the result of Zhang et al 23 Based on Eq. (23), we can investigate the state of output light in detail.…”
Section: Discussioncontrasting
confidence: 74%
“…Wang et al 22 also found that spin currents can induce second order optical Sum-Frequency generation which was verified by Werake and Zhao 1 to provide a method to detect spin currents. And very recently, Zhang et al 23 calculated the linear electro-optic coefficient induced by spin currents in GaAs and proposed to measure spin currents with Pockels effect.…”
Section: Introductionmentioning
confidence: 99%
“…According to Ref. 6, we set c = (1, 0, 0), a = (0, 1, 0) and b = (−1, 0, 0). For this configuration, using the initial conditions E 1 (0) 0 and E 2 (0) = 0, the solutions of Eq.…”
Section: Theory and Analysismentioning
confidence: 99%
“…2, 3 Since it breaks the space inversion symmetry, the spin current could also induce second order nonlinear optical effects, such as second-harmonic generation 4,5 and linear electro-optic effect. 6 More recently, it has been shown that, in the spin current induced linear electro-optic effect in semiconductors, the polarization of incident light will be changed. 6 Basing on this, one could find that the spin angular momentum will exchange between the incident light and spin currents which could be utilized to change spin current.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation